Immunological and hematological reference intervals among HIV-seronegative pregnant women in northwest Ethiopia - Genetu M; Damtie D; Workineh M; Mathewos Tebeje B; Enawgaw B; Deressa T (Dove Medical Press, 2017)
Meaza Genetu,1 Debasu Damtie,1 Meseret Workineh,1 Biniam Mathewos Tebeje,1,2 Bamlaku Enawgaw,3 Tekalign Deressa1 1Department of Immunology and Molecular Biology, School of Biomedical and Laboratory Sciences, College of Medicine and Health Science, University of Gondar, Gondar, Ethiopia; 2Molecular Parasitology Laboratory, Queensland Institute of Medical Research, Brisbane, Australia; 3Department of Hematology and Immunohematology, School of Biomedical and Laboratory Sciences, College of Medicine and Health Science, University of Gondar, Gondar, Ethiopia Background: Pregnancy is a state characterized by profound physiological hematological changes. However, hematological reference intervals being used in clinical practice in Ethiopia are derived from nonlocal general populations, despite the significant variations reported previously. The aim of this study was to determine the immunological and hematological reference intervals in healthy pregnancy among HIV-seronegative pregnant women in northwest Ethiopia.Materials and methods: A total of 200 healthy, HIV-seronegative pregnant women were enrolled from February 2015 to June 2015 in a cross-sectional study setting at Gondar University Hospital. Sociodemographic and obstetric data were collected using a structured questionnaire. Blood samples collected from each participant were used to define the immunological and hematological parameters. The mean, median, and 95% interval values were calculated for the immunological and hematological parameters. P-value <0.05 was considered statistically significant for all variables.Results: This study found that there were changes in CD4+ T-cell count, platelet count, and hematocrit (HCT) values as pregnancy advances. The calculated combined reference intervals for the absolute CD4+ T-cell count and platelet count were 712.47–760.67 and 221.25–240.14, respectively. A progressive decline in the platelet count was observed as pregnancy advanced, with 95% intervals of 224.53–253.21, 209.50–237.38, and 213.70–247.86 in the first, second, and third trimesters, respectively (P=0.27). There was a statistically significant increase in mean (±standard deviation [SD]) HCT with gestational age, being 39.18±6.70, 41.96±3.70, and 40.53±3.77 in the first, second, and third trimesters, respectively (P=0.03). The overall 95% interval for hemoglobin (HB) concentration was 12.99–13.36 g/dL, HCT 40.19%–41.49%, mean corpuscular volume (MCV) 93.33–94.63 fL, and mean corpuscular hemoglobin (MCH) 28.88–34.81 pg. Compared with the reference ranges derived from other studies, we found considerable variations in CD4+ T-cell count, HB, HCT, and MCV values.Conclusion: The findings of this study highlight the differences in immunohematological profile among pregnant women and nonpregnant women from Ethiopia and other countries, in addition to suggesting the need for such establishment of local reference values for different populations. Keywords: immunological parameter, hematological parameter, pregnant women, reference range, immunohematological reference intervals